The Effect of Audit Quality Attributes on the Cost of Equity Capital (Empirical Study on Manufacturing Companies Listed In Indonesia Stock Exchange Year 2014-2016) - Anita Wijayanti, Eka Wina Septiana Vita, Kartika Hendra Titisari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to examine and analyze the effect of audit quality attributes onthe cost of equity capital. The audit quality attributes is measure by the size of thepublic accounting firm, the industry specialty auditor and audit tenure. Meanwhile,the cost of equity capital is measure by using the PE Ratio. The population in thisstudy is all manufacturing companies listed on Indonesia Stock Exchange on 2014-2016. Sampling technique using purposive sampling method obtained by samples237 companies during the year observation. The result showed that the variablesize of the public accounting firm and the industry specialization of the auditornegatively affect the cost of equity capital. Meanwhile, audit tenure does not affectthe cost of equity capital. Based on the determination coefficient test (R2) obtainedthe coefficient of determination with adjusted R2 of 0,527. These result show that52,7% of variables cost of equity capital can be explained by the size of the publicaccounting firm, the industry specialization of auditors and audit tenure. While, therest of 47, 3% is explained by other factors outside the model in this research.Keywords: [audit quality attributes ; cost of equity capital]